1998
DOI: 10.1159/000030296
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Origin of Seminal Leucocytes Using Split Ejaculate Technique and the Effect of Leucocytospermia on Sperm Characteristics

Abstract: The origin of seminal leucocytes and their biological significance were investigated in 76 whole ejaculate samples and 27 split ejaculate samples, obtained from patients attending the Zimbabwe Family Planning Council’s Spilhaus Infertility Clinic at Harare. The leucocytes were more prevalent in fractions 1 and 2 than in fraction 3, implying that the testis, epididymis and prostate are the major sources of seminal leucocytes. The contribution from the seminal vesicles was minimal. An inverse relation is apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
2
13
0
4
Order By: Relevance
“…Semen is formed with input from the secretions of the epididymis, prostate and seminal vesicles (and bulbourethral glands) and these glands could be the source of leukocytes. Epididymis and prostate are considered the major sources of seminal leukocytes [24] . A study in patients after vasectomy indicates that the epididymis is the source of 90% seminal leukocytes [25] and studies in rat have demonstrated the presence of leukocytes in the epididymis [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Semen is formed with input from the secretions of the epididymis, prostate and seminal vesicles (and bulbourethral glands) and these glands could be the source of leukocytes. Epididymis and prostate are considered the major sources of seminal leukocytes [24] . A study in patients after vasectomy indicates that the epididymis is the source of 90% seminal leukocytes [25] and studies in rat have demonstrated the presence of leukocytes in the epididymis [26] .…”
Section: Discussionmentioning
confidence: 99%
“…We have reported in earlier studies that activated seminal leucocytes affect sperm morphology and sperm motility through the mediation of hydrogen peroxide [23]. Activated granulocytes liberate large amounts of reactive oxygen species (ROS), which damage both microorganisms and human tissues [24], and sperm damaged by ROS could lose motility and viability [18].…”
mentioning
confidence: 99%
“…Immature germ cells, spermatids and sperm cells are also present in the ejaculate of most infertile men (Gonzales et al, 1992). Seminal leucocytes have testicular origin in the epididym and prostate, and the contribution of seminal vesicles is minimal (Simbini et al, 1998). Leucospermia seems to be correlated with a decreased number and motility of the sperm, which could lead to infertility (Tolbert et al, 1987).…”
Section: Pathogenic Significance Of Leucocytes Count In the Seminal Fmentioning
confidence: 99%